Guest Editors’ Note: The Roles of Muslim Scholars in Disseminating The Quintessence of Barakah Through Multi-Disciplinary Knowledge : Editor Tamu: Peranan Sarjana Muslim dalam Pengembangan Nilai Barakah Melalui Kepelbagaian Bidang Pengetahuan - Mohd Noor , Khairunneezam; Abd Rahman , Mohd Rosmizi; Mustafa, Muhamad Zaki; Gunardi, Setiyawan; Sahid, Mualimin Mochammad (‘Abqari Journal, 2020)
This special issue reflects the focal discourses of 13 articles presented at the International Conference on Islamic Higher Education 2018 (SeIPTI 2018) which was held in Universiti Sains Islam Malaysia. All articles convey the equivalent connotation entitled The Roles of Muslim Scholars in Disseminating the Quintessence of Barakah through Multi-Disciplinary Knowledge. The topics presented discussed on multiplicity of angles in knowledge, but shared the same aim in offering benefits for the ummah (community)’s needs.